Clay and Animal Dung Ceramic Filter for Water Purification, Design, Processing and Analysis - Hussain, Mohamed A.; Mahajoub, Imad E. A.; Babiker, Mohamed Osman (Gezira Journal of Engineering and Applied Sciences, 2017)
Ceramic pot filters and packing with different materials are a household water treatment solution in areas where people rely on untreated surface water, or where the risk of contamination during water distribution and storage is high. In this Study was to design a ceramic filter from traditional materials, investigate its efficiency, to characterize of the ceramic filter materials, and compare the results of water analysis with WHO guideline and Sudanese Standard. A two design types of ceramic filter, and packing column with ceramic were prepared by clay materials and animal dung ratio; A (1:1), B (1:2), and C (2:1) for ceramic filter, and D (1:1) for structure packing and E (1:1) for random packing. The physical and chemical properties were determined for ceramic materials using absorption method, compressive strength machine and the Scanning Electron Microscope (SEM) with a coupled energy dispersive spectroscopy (EDS). The sample of water was collected from the Blue Nile. The physical and chemical properties of water were determined before and after treatment. The results of physical properties of the best ceramic materials A (1:1) showed that; absorption was 25% with flow rate of water 2.0 L/hr, and the compressive strength was 0.375 MPa. The SEM result with a coupled EDS of ceramic material was rich in pours particles and it contains dominantly oxygen, carbon, silicon and aluminum. The results of untreated water and treated by ceramic filter and Packing column with ceramic material were studied, the quality of treated water ceramic filter type A (1:1) was the best one, but for the flow properties of treated water packed column with ceramic materials was the best